Comparative analysis of two-step GA-based PV array reconfiguration technique and other reconfiguration techniques - Muhammad Ajmal A.; Ramachandaramurthy V.K.; Naderipour A.; Ekanayake J.B. (Elsevier Ltd, 2023)
Dynamic models; Electric connectors; MATLAB; Particle swarm optimization (PSO); Photovoltaic cells; Software testing; Solar power generation; Comparative analysis; Comparative studies; Dynamic reconfiguration techniques; Dynamic techniques; Electrical connection; Matlab/Simulink software; Performance analysis; Real-time application; Genetic algorithms